Prescribing pattern and awareness about anemia among in-patients in a tertiary care teaching hospital - Sarfaraz, Mohammed; Archana, A. S.; Kalwa, Bhavana; Mathew, Monish Abraham; Kuriakose, Shilpa Anna; H., Doddayya (International Journal Of Community Medicine And Public Health, 2018)
Background: Anemia is a major public health problem in India affecting people in all age groups with major consequences for human health as well as economic development. Hence the study aims to assess prescribing pattern of physicians in anemia and to create awareness among in-patients in a tertiary care teaching hospital. Methods: A prospective and observational study was carried out in 180 in-patients admitted to General Medicine department in a tertiary care teaching hospital diagnosed with anemia for 6 months. Data was collected from case sheets of patients and assessed for prescribing pattern and direct interview was conducted with patients using standardized KAP questionnaire on anemia. Results: Among 180 in-patients, 126 patients (70%) were females and 54 patients (30%) were males. As part of the therapy, folic acid with vitamin combinations (37 prescriptions) followed by elemental iron with folic acid combinations (32 prescriptions) were most prescribed drugs. KAP questions were scored appropriately and compared with hemoglobin levels. Knowledge level of patients was not significantly correlated (i.e., p=0.254) with their haemoglobin levels. There was a highly significant positive correlation (i.e., p=0.006) between attitude scores of patients and haemoglobin levels. A significant positive correlation (i.e., p=0.001) was found between practice scores of patients and hemoglobin levels. Conclusions: This study clearly showed that prescribing pattern of drugs in anemia patients’ needs to be continuously evaluated. To address the issue of anemia, the patient’s awareness should be enhanced.